Does sibling family structure matter in the emotion understanding development in preschoolers? - Aslanova, Margarita; Gavrilova, Margarita; Iurina, Elena (Frontiers in Psychology, 2024)
The objective of the study was to investigate the impact of sibling family structure —including the number of children, age gaps, presence of a twin, sibling position, and gender composition — on emotion understanding and its development in children aged 5–6 years. A total of 409 preschoolers participated. Emotion understanding was assessed using The Test of Emotion Comprehension at the baseline and then again at a 1-year follow-up. In addition to the primary variables, executive functions (comprising visual and verbal working memory and cognitive flexibility) and non-verbal intelligence were controlled for in the analysis. We used the Dimensional Change Card Sort task to assess cognitive flexibility, the Sentence Repetition and Memory for Designs subtests of NEPSY-II to measure verbal and visual working memory, respectively, and Raven’s Coloured Progressive Matrices to assess non-verbal intelligence. Sibling data were obtained from the parent surveys, while psychological assessments were administered to children by psychologists. While sibling family structure influences emotion understanding, it does not significantly affect its development over a year. A more advanced reflective emotional understanding is associated with higher cognitive flexibility and having a younger sibling, compared to other sibling positions. The results of this study offer additional knowledge for parents, educators, family therapists, and child psychologists seeking a deeper understanding of emotional development in children. These professionals can design interventions and programs that leverage sibling and peer relationships to foster emotional development, encourage collaboration through age-diverse activities, and promote caregiving roles to enhance family and group dynamics.